Imagining Maine’s Economy in a Postpandemic World - Tijerina, Stefano (Maine Policy Review, 2021)
Part of a blog he published on the Bangor Daily News website, in this commentary Stefano Tijerino describes the possible changes to international trade and Maine’s economy in the postpandemic world. From his perspective, “the way life should be” is about to be revised and redefined.